Dari Gudang Banih Ke Gudang Resi: Perubahan Sosial Petani di Desa Puntik Tengah Kabupaten Barito Kuala - Asywadie Syukur; Arif Rahman Hakim (Prodi Sosiologi FISIP ULM, 2023)
At the time of harvest, farmers in Puntik Tengah Village are faced with a situation with no choice but to sell as soon as possible to middlemen, when prices tend to be low which has a negative impact on farmers. This study aims to find out and understand how the impact of the existence of Warehouse Receipts has on the social changes of farmers in Puntik Tengah Village, Mandastana District, Barito Kuala Regency. This study uses qualitative research methods, with data collection techniques of observation, interviews, and documentation. Data analysis techniques consist of data reduction, data presentation, and data verification. This research was conducted in Puntik Tengah Village, Mandastana District, Barito Kuala Regency. The results of this study indicate that farmer changes can be seen in system changes such as yield storage space, farmers' convenience in obtaining capital and rice seeds. Increasing the economy and shifting the culture of traditional society. The change in the system can be seen from the results that farmers should get at harvest, the ease with which farmers can get rice seeds. Economic changes can be seen from the activities of farmers. Meanwhile, changes in the culture of traditional farmers can be seen from the looser dependence on capital from relatives, the resolution of agricultural barriers through the availability of warehouse receipt systems, and the function of the farmer's yard. The existence of a warehouse receipt system in Puntik Tengah Village provides high guarantees to farmers in carrying out their agriculture.